Kepimpinan perkongsian guru besar, motivasi dan tekanan kerja guru sekolah rendah berprestasi cemerlang di Kelantan - Anis Salwa, Abdullah (2019)
Headmasters' proficiency and teachers' competency crucially drive the school excellence. However, teachers nowadays are facing various challenges in educational institution environment. Hence, headmasters need to play important leadership role to improve motivation, thus reducing teachers' job stress. The effectiveness of headmasters' shared leadership in overcoming teachers' job stress was examined through a structural model which also highlighted the role of motivation as mediator as well as gender and age as moderators in excellent-performing schools in Kelantan. This cross-sectional survey involved 330 respondents by adapting Shared Leadership Perception Survey (Wood, 2005), Teacher Motivation Survey (Boyle, 2014) and Teacher Work Stress (Collie et al., 2012) instruments. The finding showed that shared leadership (M=7.90, SP=1.46) and motivation (M=7.83, SP=1.24) levels were high, while job stress level (M=3.35, SP=1.43) was low. There were significant differences in motivation level based on gender, while job stress level based on gender and age. Shared leadership had a significant positive relationship with motivation (β=.66, p<.01), as well as negative relationship with job stress (β=-.18, p<.01). Motivation contributed significant negative relationship with job stress (β=-.61, p<.01). Shared leadership and motivation contributed R²=.55 to job stress. Motivation was a partial mediator between shared leadership and job stress. Gender and age contributed moderator effect between motivation and job stress as well as shared leadership and motivation. In fact, there was a moderated-mediation effect on the relationships of shared leadership, motivation and job stress. In conclusion, the findings proved that the effective shared leadership practices could enhance motivation, thus reduce teachers' job stress. This study provides meaningful significant contribution to the school leaders and teachers in order to realize the high-performance leadership practices and upholding teaching profession which are the main contributors, as they play important roles for the changing of future education landscape towards sustaining the excellence of upcoming generations.